Effect Of Ethyl Pentanoate On Anti- Quorum Activity Of Extracellular Protein Secreted By bacillus Subtilis ATCC11774 - Nabilah Ahmad Alhadi; Nur Anis Ayunni Khalid; HairulShahril Muhamad; Maryam Mohamed Rehan; Salina Mat Radzi; Hanina Mohd Noor (Granthaalayah Publications & Printers, 2024)
Non-Indexed Publication